Зведення кам'яних фортифікацій Хотинської цитаделі за археологічними даними - Мисько, Ю.В. (Археологія і давня історія України, 2010)
У статті йдеться про основні етапи зведення кам'яних
фортифікацій цитаделі Хотинської фортеці. Статья посвящена основным этапам сооружения
цитадели Хотинской крепости. Анализ археологических, а также иконографических и письменных
источников позволяет опровергнуть распространенное в историографии мнение относительно последнего периода перестройки замка в 40-х годах XVI в. Благодаря археологическим исследованиям, проведенным экспедицией Черновицкого национального
университета в 2009—2010 гг., были обнаружены остатки юго-восточной башни XV в., разрушенной
после 1673 г. Это подтверждает, что современный вид цитадель в Хотине приобрела только во втором
десятилетии XVIII в. в результате расширения для нужд турецкого гарнизона. The article deals with the main stages of construction
of the citadel of the Khotyn fortress. The analysis of the
written, iconographic and archaeological sources allows
us to refute the widespread view in the historiography
on the last period of reconstruction of the castle in the
40th XVI century. The archaeological researches of the
expedition of Chernivtsi National University in 2009 remains
of the south-east tower (XV century) were found.
This tower was destroyed after the 1673. This confirms
that the modern view of the Khotyn citadel got only in
the second decade of the XVIII century as a result of the
rebuilding for the needs of the Turkish garrison.